Digital Campaigning and the Growing Anti-elitism: The Pirates and Beppe Grillo. Issue 1 (June 2013) - Hartleb, Florian
In the digital age, new ways of interaction provide a new type of public sphere which has dramatically changed party politics. This includes not only the modernisation and professionalisation of mainstream political parties but also paves the way for new challengers and a new dimension of campaigning. The current examples, the Pirate Party, especially in Germany, and the Five Star Movement of Beppe Grillo, show at least short-term potential. The Pirate Party caused a media hype about the young activists. Grillo transcended the borders between comedy and politics without the helping hand of the traditional media, which ignored him. The threat for representative democracies lies in the growing anti-elitism which is combined in the Pirates and Grillo. Mainstream political parties should indicate that the claim for a new participatory politics beyond right and left is a utopian one, while attacking the way that party politics works.